Cognitive Aspects Of The Notion Of Dimunitiveness - Kamola Makhmadmurodova; Akhmadalieva Khosiyatposhsho Abdukhayotovna (Zien Journals, 2024)
Cognitive linguistics is one of the relevant and not yet fully explored areas of linguistics. Also, research in the fields of pragmatic and cognitive linguistics is one of the most urgent issues today. The purpose of this article is to research and conduct small studies about the specific role of pragmatics and cognitive in Linguistics.
Keywords: cognitive linguistics; concept; conduct; cognition